Hand Surgery in Malaysia - Ahmad, Tunku Sara; Ahmad, Amir Adham; Abdullah, Shalimar (Journal of Hand and Microsurgery, 2020)
We have all heard the old aphorism, “Necessity is the mother of invention.” While the provenance of the proverb is uncertain, its truth is not in doubt. This is true for the development of hand surgery in Malaysia. As part of the management for leprosy, patients with high ulnar nerve palsies were managed by the pioneers of hand surgery in Malaysia. They did tendon transfers to improve the quality of life of these patients. Since then, hand surgery in Malaysia have grown leaps and bounds. From a small humble beginning in the suburb of Sungai Buloh to organizing the 10th Congress of Asian Pacific Federation of Societies for Surgery of the Hand, hand surgery in Malaysia will only get better with time.
Keywords: Malaysia; hand surgery; history; MSSH; APFSSH; WALANT